Appendicular osteology of Skorpiovenator bustingorryi (Theropoda, Abelisauridae) with comments on phylogenetic features of abelisaurids. (31st December 2022) - Cerroni, Mauricio A.; Baiano, Mattia A.; Canale, Juan I.; Agnolín, Federico L.; Otero, Alejandro; Novas, Fernando E.
Abstract : Skorpiovenator bustingorryi is a derived abelisaurid theropod represented by a fairly complete skeleton from the Late Cretaceous sedimentary beds of north-western Patagonia. Although some features were described in the original paper, mainly related to the skull, the appendicular anatomy remains undescribed. The aim of the present contribution is to provide a detailed description and analysis of the available appendicular bones, including comparisons with other ceratosaurian theropods close to Skorpiovenator . In this way, new autapomorphies emerged to further distinguish Skorpiovenator from its relatives. Furthermore, a comprehensive phylogenetic analysis was performed and several characteristics of the hind limb, in particular some of the autopodium, resulted in the identification of new apomorphic traits for Ceratosauria and Abelisauridae. These features might prove to be useful for future phylogenetic analyses and may help to resolve the still confusing and debated internal relationships of abelisaurid theropods.